2003
DOI: 10.1002/chin.200324100
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Profile of 5‐Imidazolinones, Sulfonamides, Azomethines, 2‐Azetidinones and Formazans Derived from 2‐Amino‐3‐cyano‐5‐(5′‐chloro‐3′‐methyl‐1′‐phenylpyrazol‐4′‐yl vinyl)‐7,7‐dimethyl‐6,7‐dihydrobenzo(b)thiophenes.

Abstract: Pyrazole derivatives Pyrazole derivatives R 0180Synthesis and Antimicrobial Profile of 5-Imidazolinones, Sulfonamides, Azome- thines, 2-Azetidinones and Formazans Derived from 2-Amino-3-cyano-5-(5'-chloro-3'-methyl-1'-phenylpyrazol-4'-yl vinyl)-7,7-dimethyl-6,7-dihydrobenzo(b)thiophenes. -Fifty title compounds of type (III), (V), (VII), (IX), and (XI) are prepared and tested for their antimicrobial activity. Some compounds show antimicrobial activities comparable to standard drugs. -(DESAI, J. M.; SHAH*, V. H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This showed that the compounds were obtained in a pure state. IR and 1 Formazans have been reported to possess an attractive antimicrobial activity [6][7][8][9][10][11][12][13][14][15]. Further to confirm this, the zone of inhibition value of the all the synthesized compounds (Ia-Id) were showed good antifungal and antibacterial activity when compared to that of the standard drug.…”
Section: Docking Methodologymentioning
confidence: 77%
See 1 more Smart Citation
“…This showed that the compounds were obtained in a pure state. IR and 1 Formazans have been reported to possess an attractive antimicrobial activity [6][7][8][9][10][11][12][13][14][15]. Further to confirm this, the zone of inhibition value of the all the synthesized compounds (Ia-Id) were showed good antifungal and antibacterial activity when compared to that of the standard drug.…”
Section: Docking Methodologymentioning
confidence: 77%
“…Formazans have been studied widely owing to their ready ease of access, assorted chemical reactivity and its biological activities [4,5]. Formazans have attracted attention because of their diverse medicinal applications such as antimicrobial [6][7][8][9][10][11][12][13][14][15], (including antiviral, antifungal, antibacterial), antifertility [16], analgesic and anti-inflammatory [17][18][19][20], antitubercular [21,22], anticonvulsant [23,24], antiparkinsonian [25,26], anticancer, anti HIV [27][28][29], antiproliferative [30,31] and antihyperglycemic [32] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Only recent reports that have been published during the period from 1980 to 2013 are covered. Compounds of type 4 ( Chart 1 ), which were erroneously named, in some articles [36–40] as formazans, will not be included in this review as they are amidrazone derivatives and not formazans.…”
Section: Introductionmentioning
confidence: 99%
“…Formazans have been found to possess important medical applications due to their various activities such as antiviral,[ 1 ] antimicrobial,[ 2 3 ] anti-inflammatory, analgesic,[ 4 ] antifungal,[ 5 ] anticancer, anti-HIV,[ 6 ] etc. Several formazans showed promising anti-fertility,[ 7 ] anti-parkinsonian[ 8 ] and anticonvulsant activities.…”
Section: Introductionmentioning
confidence: 99%